RETRACTED: The Relationship between Explanatory Ability and Collegiate Learning Assessment Task - Monika Lintang Laksmi; Baskoro Adi Prayitno; Meti Indrowati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
RETRACTED: The editorial board of JPtpp has officially retracted the article "The Relationship between Explanatory Ability and Collegiate Learning Assessment Task" (Vol. 9, No.9, pp.398-409, September, 2024), due to a violation of publication ethics. Following a thorough review, the editor confirmed that this paper represents a duplicate publication. It contains redundant material previously published in JPtpp Vol. 8, No.2, pp.100-107, February 2023, URL: https://journal.um.ac.id/index.php/jptpp/article/view/21399, under the title "The Relationship between Explanatory Ability and Collegiate Learning Assessment Task". In accordance with institutional policies, the digital version of this document has been removed from previously published, and all citations or references to this paper should be discontinued. The literature study discusses the relationship between explanatory ability and the Collegiate Learning Assessment (CLA) Task. The method used is a study of the literature related to explanatory ability and the CLA Task, the literature studied from 2015 to 2022. The literature study results are CLA Task with an open-ended question, problem-based situations, and problem-solving can be used as an assessment of explanatory abilities that consist of indicators for justifying procedures, stating results, and presenting explanations. The achievement of the three indicators of explanatory ability that will be empowered with the CLA Task needs the help of an electronic module for media learning.